Effect of aging on the dissolution stability of glibenclamide/β- cyclodextrin complex - Jayachandra Babu R.; Pandit J.K. (My University, 2025)
The effect of aging on the physicochemical stability of glibenclamide (GB)/β-cyclodextrin (CD) systems and tablets made with CD-complexed GB was studied. Infrared (IR) spectrometry and X-ray diffraction analyses showed that the properties of the products were unaffected even after a storage period of 4 years, except that the crystallinity of GB/CD physical mixture was decreased with aging. The dissolution rate of the kneaded mixture, inclusion complex, and tablets made with the inclusion complex were unaffected on storage for 4 years. Thus, the age-related dissolution problems of GB can be overcome by utilizing the GB/CD complex in the tablet dosage form.